Propuesta de ruteo de vehículos con flota heterogénea y ventanas de tiempo (HFVRPTW) aplicada a una comercializadora pyme de la ciudad de Cali (2018)
This article addresses the problem of vehicle with heterogeneous fleet routing and windows of time (HFVRPTW) to solve a real problem applied to a small marketer of products food additives in the city of Cali, which must meet a set of customers with popular demands, where each client must be attended within a predefined time interval. The model was developed in three phases: the characterization of the current programming process route and distribution, the adaptation of the mathematical model and solution of the model by means of heuristic method of savings, which adapts efficiently to the problem and results with substantial improvements related to the number of routes of up to 40 % for vehicle type NHR, decrease in the distance of 50 % for the Dmax vehicle and decrease in total costs of transportation for 2 types of vehicles.